Factores que afectan el rendimiento reproductivo de las vacas lecheras que pertenecen al proyecto UTC GEN de Latacunga occidental en el periodo 2023 - Tenecota Valencia, Washington Alexander (2024)
The producers of the UTC gen project in the western area of Latacunga are concerned due to low reproductive efficiency, as they cannot obtain offspring every year due to long periods of open days. Therefore, the factors affecting the reproductive performance of cows during the 2023 period were analyzed. The considered parishes were four: Eloy Alfaro, Pastocalle, Toacaso, and Once de Noviembre from October 2023 to February 2024. The population consisted of 80 animals, including cows and heifers. Additionally, the initial gynecological diagnosis resulted in 36,25% of animals being acyclic and 47,50% cyclic, with the presence of ovarian cysts at 1,25% and 15% of females pregnant by bull. In the second diagnosis, the number of acyclic animals decreased to 18,75%, possibly due to vitamin, mineral, and tonic supplementation. Furthermore, a total of 46 artificial inseminations were performed, resulting in 60,87% pregnant, and heat regression or reabsorptions and abortions in 39,17% of the study population.